THE CREATIVE STATUS OF ARTISTIC WRITING AS THE FUNDAMENTAL VALUE OF NEOTRADITIONALISM (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-107-114Abstract. Neotraditionalism (the term suggested by Thomas Eliot's essay “Tradition and Individual Talent”) is considered not as one of the many “isms” of the crisis of the 20th century, but as a saving trend in artistic writing, overcoming this epoch-making crisis that led to a postmodern “consumer society” and promising the preservation of a high culture of artistic writing. The value of this trend is seen in classical aesthetics, its beginning was laid by Alexander Baumgarten, who discovered and justified the truly creative (in the full sense of the word) nature of aesthetic activity, devalued in our time by numerous provocative practices of the avant-garde. Special attention is paid to acmeism, that promotes the concept of “heralding” (replacing Kant's “genius”) to characterize truly creative acts. The radical opposition of postmodernism and the value system of artistic writing has been revealed and approved in the “Big Time” by Mandelstam, Akhmatova, Tsvetaeva, the late Pasternak, Brodsky and others, up to the modern continuators of neotraditionalism.Key words: neotraditionalism, postmodernism, creativity, artistic writing, aesthetics